Caracterización edáfica y climática de QUERCUS SUBER L. EN LAS PROVINCIAS DE SALAMANCA Y ZAMORA - JOVELLAR LACAMBRA, L C; A., BLANCO ANDRAY; SANTOS FRANCÉS, F (IV Congreso Forestal Español, 2005)
Ecological parameters characterizing cork oak forest in west-central Spain (Salamanca y Zamora) were obtained. From those parameters, central and marginal habitats for Quercus suber stands were established for this region of Spain. Main soils and climate types for the present sites of these forests have been identified as well
Keywords: Cork Oak Forest; ecology; habitat; Quercus suber; Salamanca; Zamora

Invasión del matorral por Genista hystrix en una dehesa salmantina (España) - Caro Domínguez, Francisco; Sánchez Anta, María Ángeles; Tarazona Lafarga, Teresa (Ecología Aplicada, 2004)
The invasion of Genisto hystricis-Cytisetum multiflori shrubs in a Salamancan "dehesa" (Quercus forest with low density), was studied using permanent quadrat and transect methodology. The results indicate that, of all shrub species, Genista hystrix Lge. is the predominant invading species in this sclerophyllous formation, due to its growth rate and phenomorphology. The overall invasion rate of this shrub in the "dehesa" has been calculated to be approximately 2.26 m 2 per year
Keywords: "dehesa"; Cytisus multiflorus (L'Hèr.) Sweet.; Cytisus scoparius (L.) Link; dynamics; Genista hystrix Lge.; Invasive species; Quercus rotundifolia Lam.; Salamanca; sclerophyllous; Shrubs

Invasión del matorral por Genista hystrix en una dehesa salmantina (España) - Caro Domínguez, Francisco; Sánchez Anta, María Ángeles; Tarazona Lafarga, Teresa (Ecología Aplicada, 2004)
The invasion of Genisto hystricis-Cytisetum multiflori shrubs in a Salamancan "dehesa" (Quercus forest with low density), was studied using permanent quadrat and transect methodology. The results indicate that, of all shrub species, Genista hystrix Lge. is the predominant invading species in this sclerophyllous formation, due to its growth rate and phenomorphology. The overall invasion rate of this shrub in the "dehesa" has been calculated to be approximately 2.26 m 2 per year
Keywords: "dehesa"; Cytisus multiflorus (L'Hèr.) Sweet.; Cytisus scoparius (L.) Link; dynamics; Genista hystrix Lge.; Invasive species; Quercus rotundifolia Lam.; Salamanca; sclerophyllous; Shrubs

de la quema, corte, arranque, abandono o pastoreo del matorral de escoba blanca (Cytisus multiflorus) sobre la producción y estructura de la comunidad herbácea - Fernández-Santos, B; Gomez Gutiérrez, J M; Garcia Mares, R T (Pastos, 1992)
The effects of burning, cutting , pulling out, field abandonment or grazing on the pro- duction and structure of a dehesa pasture invaded by Cytisus multiflorus were studied. Significant differences in the biomass of herbaceous species were found between pastu- res and treatments when cutting was done in February. The highest total biomass pro- duction was in the "abandoned" plot. No differences were found between the burned and cut plots. All the treatments, except abandonment, gave rise to higher biomass in herbaceous plants compared to control plots, i.e. on which grazing was continued. After 3 years there was no effect of treatment on the appearance of new species. A decrease in species number was observed with the burned plot being the least affected. The área with traditional grazing showed the highest diversity, specific heterogeneity and propor- tion of leguminous species. The negative effect of cutting the above-ground biomass in winter is discussed. Key
Keywords: Biomass production; Community structure; Human disturbances treatments; Matorral pasture; Salamanca

FITOMASA SUBTERRÁNEA Y AÉREA EN PASTOS DE DEHESA - Puerto Martín, A; Puerto, A (Pastos, 1992)
A study has been conducted on the spatial variations undergone by root biomass, aerial phytomass and the root/shoot ratio in grassland communities (dehesa systems). These variations are governed by the prevailing gradients: topographic and the effect of the tree canopy. The greatest biomass, both underground and aerial, and the lowest root/shoot ratio are usually found in the more fertile sites (deposition sector of slope) and shaded áreas (under the crowns of the trees), in contrast to the results of some researchs performed in cultures or at the laboratory. In the case of natural or semi-natural groupings of herba- ceous species in severe environments, the adaptive responses of each species appear to predomínate over any generalized type of response. Key
Keywords: España; fitomasa; Grasslands; influencia del arbolado; ladera; pastos; phytomass; Salamanca; Salamanca (Spain); slope; tree canopy ¡nfluence